Absorbed dose in the operator's brain in interventional radiology practices: evaluation through KAP value conversion factors. (August 2020) - Ferrari, Paolo; Jovanovic, Zoran; Bakhanova, Elena; Becker, Frank; Krstic, Dragana; Jansen, Jan; Principi, Sara; Teles, Pedro; Clairand, Isabelle; Knezevic, Željka
Highlights: Monte Carlo simulations are employed to estimate brain exposure to medical staff in interventional radiology. For the first operator there is no difference in the exposure between the right and left parts of the brain. For the second operator left part of the brain exposure is up to two times higher than right one. Outcomes of the simulations are in agreement with the measurements results reported by other investigators. The second operator's results could be used for an estimation of brain exposure of operators in interventional cardiology. A rough estimation of the dose to the brain in interventional radiology is provided. Abstract: In order to address the recent concerns over a possible increasing in brain tumour mortality among interventional radiologists and cardiologist, this work evaluated the exposure conditions of the operator's brain during interventional procedures using Monte Carlo simulations with anthropomorphic phantoms. The absorbed doses in several predefined segments of the operator's brain were estimated in a typical interventional radiology irradiation scenario. The doses were normalized to the KAP values simulated for ten X-ray beam qualities and four projections (PA, RAO 25°, LAO 25° and CRA 25°). For the interventional radiology scenario, because of the position of the operator, no difference was found in the exposure between the left and right regions of the brain for the first operator. However, for the second operator standing at a farer distance from the tube, the exposure of the left part of the brain is up to two times higher than that of the right part. The results are in agreement with dose measurements reported in the literature. The conversion factors, obtained as the absorbed dose per KAP, can be used to obtain a first estimate of the exposure of the brain of the operators during interventional procedures.